The impact of Arctic warming on the midlatitude jet‐stream: Can it? Has it? Will it?. (13th March 2015) - Barnes, Elizabeth A; Screen, James A
Abstract : The Arctic lower atmosphere has warmed more rapidly than that of the globe as a whole, and this has been accompanied by unprecedented sea ice melt. Such large environmental changes are already having profound impacts on the flora, fauna, and inhabitants of the Arctic region. An open question, however, is whether these Arctic changes have an effect on the jet‐stream and thereby influence weather patterns farther south. This broad question has recently received a lot of scientific and media attention, but conclusions appear contradictory rather than consensual. We argue that one point of confusion has arisen due to ambiguities in the exact question being posed. In this study, we frame our inquiries around three distinct questions: Can Arctic warming influence the midlatitude jet‐stream? Has Arctic warming significantly influenced the midlatitude jet‐stream? Will Arctic warming significantly influence the midlatitude jet‐stream? We argue that framing the discussion around the three questions: Can it?, Has it?, and Will it? provides insight into the common themes emerging in the literature as well as highlights the challenges ahead. WIREs Clim Change 2015, 6:277–286. doi: 10.1002/wcc.337 This article is categorized under: Paleoclimates and Current Trends > Detection and Attribution Climate Models and Modeling > Knowledge Generation with Models